Egg perivitelline fluid of the invasive snail Pomacea canaliculata affects mice gastrointestinal function and morphology - Giglio, Matías Leonel (2018)
Background. Species beloging to the genus Pomacea (Ampullariidae), often referred as apple snails are freshwater, amphibious snails native to South, Central and North America. Some species such as P. canaliculata have become a driver of ecosystem changes in wetlands and an important rice and taro pest after its introduction to Asia and other parts of the world. Females deposit colored egg clutches above the waterline, a reproductive strategy that exposes the eggs to harsh conditions and terrestrial predation. However, eggs have no reported predators in their native range, probably because of the acquisition of unparalleled biochemical defenses provided by a set of proteins (perivitellins) that nourish embryos and protect them from predators and abiotic factors. Notably, ingestion of egg perivitelline fluid (PVF) decreases rat growth rate and alters their gastrointestinal morphology. The aim of the study is to determine the effect of apple snail egg PVF on mice gut digestive activity, morphology and nutrient absorption.Methods. Carbohydrate digestion by intestinal disaccharidases (sucrase-isomaltase and maltase-glucoamylase) was evaluated ex vivo in mice gavaged with 1 or 4 doses of PVF. Changes in gut morphological and absorptive surface were measured. In addition, alteration on nutrient absorption rates, transport pathways and intestinal permeability was evaluated by luminal perfusions of small intestine with radiolabeled L-proline (absorbed by paracellular and transcellular pathways) and L-arabinose (absorbed exclusively by paracellular pathway).Results. Perivitelline fluid affected mice displayed significant morphological changes in the small intestine epithelium inducing the appearance of shorter and wider villi as well as fused villi. This resulted in a diminished absorptive surface, notably in the proximal portion. Likewise, the activity of disaccharidases diminished in the proximal portion of the intestine. Total absorption of L-proline increased in treated mice in a dose-dependent manner. There were no differences neither in the ratio of paracellular-to-transcellular absorption of L-proline nor in gut permeability as revealed by the clearance of L-arabinose.Discussion. Oral administration of apple snail PVF to mice adversely alters gut morphophysiology by reducing the intestinal absorptive surface, affecting enzymes of sugar metabolism and increasing the absorption rate of nutrients without affecting the relative contribution of the absorption pathways or gut permeability. These results further support the role of PVF in passive anti-predator defenses in Pomacea snail eggs that target the digestive system.